Hubungan Kejadian Dry Eye Syndorme pada Pasien Glaukoma terhadap Lama Penggunaan Obat Tetes Mata Topikal - Yunani Setyandriana; Muhammad Baharuddin Yusuf (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Introduction: Glaucoma is a leading cause of irreversible blindness that requires long-term treatment using topical eye drops. Prolonged use, especially those containing preservatives, may cause ocular surface damage and lead to dry eye syndrome, affecting patients’ quality of life. Purpose: This study aimed to determine the relationship between long-term use of topical eye drops and the incidence of dry eye syndrome in glaucoma patients. Methods:This study used an observational analytic design with a cross-sectional approach involving 52 respondents. Data were collected using the Ocular Surface Disease Index (OSDI) questionnaire to assess dry eye symptoms. Data were analyzed using univariate and bivariate analysis with a significance level of p < 0.05. Results: The majority of respondents were female (73.1%) and aged 50 –59 years (30.8%). Most respondents experienced severe dry eye syndrome (32.7%). The bivariate analysis showed a p-value of 0.001 (p < 0.05), indicating a significant relationship between long-term use of eye drops and dry eye syndrome. Conclusion: There is a significant relationship between long-term use of topical eye drops and the incidence of dry eye syndrome in glaucoma patients.